Effects of the hydrodynamic environment and oxygen mass transfer on plant cell growth and milk-clotting protease production in a stirred-tank reactor - Raposo, Sara (2014)
Industrial-scale plant cell based bioprocesses are limited because of technological challenges associated with mass transfer and mixing in the heterogeneous broth, which typically displays non-Newtonian characteristics. Cultures of Centaurea calcitrapa cells, presenting milk-clotting activity, were established in a 7-L stirred-tank reactor (STR), keeping the initial mass transfer conditions constant, to gain a better understanding of the effects of the hydrodynamic environment and mass transfer on protease production. Cell suspensions grown in an STR equipped with one single marine propeller or two Rushton turbines showed the highest protease activities and biomass production, corresponding to the adequate mass transfer achieved under the tested bioreactor conditions. The key factors improving milk-clotting protease production in a bioreactor were an efficient mass transfer and good bulk mixing without the formation of stagnant zones, while a compromise had to be established in relation to the hydrodynamic shear conditions.